PENGARUH KEPERCAYAAN TERHADAP BAZNAS, PENDAPATAN DAN PENGETAHUAN ZAKAT TERHADAP MINAT MASYARAKAT MEMBAYAR ZAKAT MAL DI KABUPATEN BOJONEGORO - Muhammad Aril Fahad (Jurnal Ilmiah Mahasiswa FEB, 2019)
The influence of trust to Baznas, revenue, and zakat knowledge on people’s interest in paying zakat Al-mal in Bojonegoro regency. This research uses quantitative research methods. The analysis technique used is multiple linear regression analysis. The data obtained are primary data from the distribution of questionnaires directly to the respondents of the results of this study indicate that the variable trust to Baznas, revenue and zakat knowledge zakat has a significant effect on people's interest in paying Zakat Al-Mal in Bojonegoro district. Kata kunci:Trust, Income, Zakat mal, Baznas.